THE FEASIBILITY ANALYSIS OF THE FLOATING NET CAGE BUSINESS BY REVIEWING THE ECONOMIC CALCULATIONS AND CARRYING CAPACITY OF THE KAMPAR RIVER ENVIRONMENT IN BULUHCINA VILLAGE, SIAK HULU DISTRICT, KAMPAR REGENCY - Yudho Harjoyudanto; Rifardi Rifardi; Windarti Windarti; Andri Hendrizal; Rina D'rita Sibagariang (Berkala Perikanan Terubuk, 2019)
In recent years, many net cages for aquaculture activities, especially for culturing Wallago leeri and Mystus numerus are placed along the Kampar River, especially in the Buluhcina Village. The remain of fish feed, namely rotten chicken flesh have polluted the water. This study aimed to identify the cage culture profile; to analyze the feasibility of the business and the carrying capacity of the environment. This research was conducted in August 2016 – March 2017. There are three observation stations,  Station 1 (before the cage area), Station 2 (the cage area) and Station 3 (after the cage area). Sampling was conducted once. The length of the river is 1.4 Km and 594 single unit net cages are placed along 1,2 Km river. Among the cages, 570 units (96% )are used to the culture of W. leeri,  19 units (3.2%) for M. numerus and the rest, 3 units are for rearing Pangasius sp. and Oreochromis niloticus (1 unit). The carrying capacity of the waters is 496.1 tons/year. The current annual production of W. leeri is 228 tons/year, it is less than the maximum potency.  It is predicted that the culture can be increased by 258.5 ton/year or 646 cages. The recent RCR value is 1.120, indicates that this business is profitable and it could be continued.